2016
DOI: 10.1039/c5cp06890h
|View full text |Cite
|
Sign up to set email alerts
|

Boosting water oxidation layer-by-layer

Abstract: ), moving from acidic to alkaline conditions. Bulk electrolysis experiments revealed that the IrO 2 /PDDA films were stable and adherent under acidic and neutral conditions but degraded in alkaline solutions. Oxygen was evolved with Faradaic efficiencies approaching 100% under acidic (pH 1) and neutral (pH 7) conditions, and 88% in alkaline solutions (pH 13).This layer-by-layer approach forms the basis of future large-scale OER electrode development using ink-jet printing technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…This loss of stability, which is marginal at the working conditions employed (low potentials), most likely takes place due to the swelling of the polymer and the breakdown of the electrostatic interactions binding the layers together on the electrode surface. Noticeably, all CVs in Figures A,B resemble those obtained previously in acidic aqueous media exhibiting Ir(III)‐Ir(III)/Ir(IV)‐Ir(IV) and Ir(IV)‐Ir(IV)/Ir(IV)‐Ir(V) redox transitions at 0.78 V and 1.07 V, respectively, and the onset potential for the WOR in the range 1.17–1.32 V. The formation of oxygen upon oxidation at potentials beyond this value was confirmed by gas chromatography (Supporting Information). A closer inspection of the CVs in Figure A (inset) reveals that at high water content ( X H 2 O≥0.6), the voltammetry remains practically unaffected.…”
Section: Figuresupporting
confidence: 80%
See 3 more Smart Citations
“…This loss of stability, which is marginal at the working conditions employed (low potentials), most likely takes place due to the swelling of the polymer and the breakdown of the electrostatic interactions binding the layers together on the electrode surface. Noticeably, all CVs in Figures A,B resemble those obtained previously in acidic aqueous media exhibiting Ir(III)‐Ir(III)/Ir(IV)‐Ir(IV) and Ir(IV)‐Ir(IV)/Ir(IV)‐Ir(V) redox transitions at 0.78 V and 1.07 V, respectively, and the onset potential for the WOR in the range 1.17–1.32 V. The formation of oxygen upon oxidation at potentials beyond this value was confirmed by gas chromatography (Supporting Information). A closer inspection of the CVs in Figure A (inset) reveals that at high water content ( X H 2 O≥0.6), the voltammetry remains practically unaffected.…”
Section: Figuresupporting
confidence: 80%
“…To achieve this, we utilized fluorinated tin oxide (FTO) electrodes modified sequentially layer‐by‐layer with the positively charged polymer poly(diallydimethylammonium chloride) (PDDA) and negatively charged citrate‐stabilized IrO 2 NPs (see Figure ). In a separate study, we clearly demonstrated the electrocatalysis of the WOR in aqueous media using these layer‐by‐layer modified FTO electrodes that exhibited good operational stability, remaining active over a wide pH‐range . Herein, these electrodes are utilized as a platform to study the electrocatalysis of the WOR in water/ACN mixtures.…”
Section: Figurementioning
confidence: 92%
See 2 more Smart Citations
“…Finally, based on our long-term electrolysis and coupled XPS investigations, tuning the affinity of the complex for the polarized electrode surface may be an interesting aspect of catalyst developments, since it has been demonstrated with appropriate polyelectrolyte additives that the layer-by-layer approach is a viable strategy to fabricate OER electrodes. 48,69 …”
Section: Discussionmentioning
confidence: 99%